Efektivitas Penggunaan Lampu LED Biru terhadap Hasil Tangkapan Bubu di Perairan Desa Tepa, Maluku Barat Daya - Donal Noija; Hehanussa, Kedswin G.; Ronald Darlly Hukubun (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The effectiveness of fish traps (bubu) largely depends on the gear’s ability to attract fish, especially in environments with high competition and dynamic water conditions (Hehanussa et al., 2020). One innovative method that has been increasingly developed over the past few decades to enhance the attractiveness of fishing gear is the use of light attractors. Artificial light, particularly from Light Emitting Diode (LED) lamps, has been proven to improve catch rates across various fishing gears, including nets, longlines, and traps. LEDs are favored due to their high energy efficiency, long lifespan, and availability in a wide range of light spectra. This study aims to evaluate the effect of using blue Light Emitting Diode (LED) lamps on the catch performance of fish traps in the waters of Tepa Village, Southwest Maluku Regency. The research was conducted from August to October 2024 using two fish traps: one equipped with a blue LED lamp and one without a lamp as a control. Results showed that the trap equipped with the blue LED accounted for 69.83% of the total fish caught, significantly higher than the control trap (30.17%). Statistical tests revealed a significant difference in the number of fish caught (p = 0.01) but not in species composition (p = 0.38). The dominant species caught belonged to the families Scaridae, Acanthuridae, and Naso. These findings indicate that blue LED technology is effective in enhancing the efficiency of fishing gear in an environmentally friendly and sustainable manner.